Molecular characterization of norovirus infection responsible for acute diarrhea in Congolese hospitalized children under five years old in Brazzaville, Republic of Congo. (November 2019) - Mikounou Louya, Vivaldie; Vouvoungui, Christevy; Koukouikila-Koussounda, Félix; Veas, Francisco; Kobawila, Simon Charle; Ntoumi, Francine
Graphical abstract: Highlights: Norovirus is considered to be the second leading cause of morbidity and mortality among children under five with severe diarrheal infection in Africa. Norovirus infection was detected only in Congolese children under 24 months. Higher prevalence of norovirus infection in dry season. GII genogroup was the most prevalent in Congolese samples. Abstract: Background: Acute diarrhea is a leading cause of morbidity and mortality among children under five worldwide. As no published data is available on the occurrence of this infection in the Republic of Congo, this study aimed at (1) determining the prevalence and (2) characterizing genotypes of norovirus strains in Brazzaville. Methods: From June 2012 to June 2013, stool samples were collected from hospitalized young children with acute gastroenteritis. A total of 545 samples were tested for GI and GII norovirus infections using nested duplex reverse-transcription–polymerase chain reaction and sequencing. Results: The GI and GII norovirus infection were detected in 148 samples. Males (28%) were not significantly more infected than females (25%). Norovirus infection was found exclusively in children aged under 24 months with a higher prevalence (P = 0, 048) in the age group of 7–12 months, and throughout the year with a peak in August and September. Genetic diversity of norovirus strains revealed that GII was the most prevalent (87%). No risk factor was significantly associated with norovirus infection. Conclusion: This study showed that noroviruses are important agents responsible for acute diarrhea in Congolese children and highlights the importance of continued surveillance.